Leveraging AI for Enhanced Operational Risk Management in Sports Events - Jibraili Malak; Rharib Abderrahim; Jibraili Zineb (ITM Web of Conferences)
This article explores the integration of artificial intelligence (AI) into operational risk management at sporting events. It highlights the major advances brought about by AI, particularly in managing crowd safety, optimising logistics flows, and improving ticketing and procurement systems. However, challenges remain, such as the reliability of the technologies deployed, real-time incident management, and stakeholder resistance to change. The article uses semi-structured interviews with international experts to gather informed perspectives on current and future applications of AI in this field. The results reveal that, although AI offers many opportunities to minimise operational failures, concerns remain about the complexity of algorithms and the management of real-time data. Despite these obstacles, the paper concludes that future prospects are promising, with potential innovations such as the automation of critical processes and the prediction of operational incidents.